Enriched environment attenuates hippocampal theta and gamma rhythms dysfunction in chronic cerebral hypoperfusion via improving imbalanced neural afferent levels - Zheng, Jiaxin; Peng, Sisi; Cui, Lingling; Liu, Xi; Li, Tian; Zhao, Zhenyu; Li, Yaqing; Hu, Yuan; Zhang, Miao; Xu, Linling; Zhang, JunJian (Frontiers in Cellular Neuroscience, 2023)
Chronic cerebral hypoperfusion (CCH) is increasingly recognized as a common cognitive impairment-causing mechanism. However, no clinically effective drugs to treat cognitive impairment due to CCH have been identified. An abnormal distribution of neural oscillations was found in the hippocampus of CCH rats. By releasing various neurotransmitters, distinct afferent fibers in the hippocampus influence neuronal oscillations in the hippocampus. Enriched environments (EE) are known to improve cognitive levels by modulating neurotransmitter homeostasis. Using EE as an intervention, we examined the levels of three classical neurotransmitters and the dynamics of neural oscillations in the hippocampus of the CCH rat model. The results showed that EE significantly improved the balance of three classical neurotransmitters (acetylcholine, glutamate, and GABA) in the hippocampus, enhanced the strength of theta and slow-gamma (SG) rhythms, and dramatically improved neural coupling across frequency bands in CCH rats. Furthermore, the expression of the three neurotransmitter vesicular transporters—vesicular acetylcholine transporters (VAChT) and vesicular GABA transporters (VGAT)—was significantly reduced in CCH rats, whereas the expression of vesicular glutamate transporter 1 (VGLUT1) was abnormally elevated. EE partially restored the expression of the three protein levels to maintain the balance of hippocampal afferent neurotransmitters. More importantly, causal mediation analysis showed EE increased the power of theta rhythm by increasing the level of VAChT and VGAT, which then enhanced the phase amplitude coupling of theta-SG and finally led to an improvement in the cognitive level of CCH. These findings shed light on the role of CCH in the disruption of hippocampal afferent neurotransmitter balance and neural oscillations. This study has implications for our knowledge of disease pathways.